Reclassification of Hepatocellular Cancer With Neural-Related Genes - Zhang, Yi-Gan; Jin, Ming-Zhu; Zhu, Xiao-Ran; Jin, Wei-Lin (Frontiers in Oncology, 2022)
Neural infiltration is a critical component of the tumor microenvironment; however, owing to technological limitations, its role in hepatocellular cancer remains obscure. Herein we obtained RNA-sequencing data of liver hepatocellular carcinoma (LIHC) from The Cancer Genome Atlas (TCGA) database and performed a series of bioinformatic analyses, including prognosis analysis, pathway enrichment, and immune analysis, using the R software packages, Consensus Cluster Plus and Limma. LIHC could be divided into two subtypes according to the expression of neural-related genes (NRGs); moreover, there are statistic differences in prognosis, stage, and immune regulation between the two subtypes. The prognostic model showed that high expression of NRGs correlated with a poor survival prognosis (P<0.05). Further, CHRNE, GFRA2, GFRA3, and GRIN2D was significantly correlated with LIHC clinical prognosis, clinical stage, immune infiltration, immune response, and vital signaling pathways. There was nerve-cancer crosstalk in LIHC. Reclassification of LIHC based on NRGs expression may prove beneficial to clinical practice. CHRNE, GFRA2, GFRA3, and GRIN2D may serve as potential biomarker for liver cancer prognosis or immune response.